One-way or return? Explaining group-specific return intentions of recently arrived Polish and Turkish immigrants in Germany. (23rd January 2018) - Steinmann, Jan-Philip
Abstract: This article analyses return intentions of new migrants on both the individual and the group level. The aim is, firstly, to systemize factors commonly discussed in studies on (re)migration to explain newcomers' return intentions on the individual level. Secondly, I ask whether these identified factors account for differences in return intentions between two ethnic groups. The hypotheses are tested with data from the SCIP-project ('Socio-cultural integration processes among new immigrants in Europe') collected from new Polish and Turkish arrivals in Germany. The findings reveal that initial motives for migration, as well as (economic, social, and cultural) ties to receiving and origin countries, contribute to explaining newcomers' return plans, whereas perception of ethnic boundaries plays a minor role. Moreover, group-specific return intentions can be explained by the fact that Poles and Turks differ in their motives for migration and their endowment with ties. These findings reflect the impact of the immigration regulations that shape the composition of newcomers migrating to Germany, which, in turn, has an influence on their return intentions. In the conclusion, implications for migration theories are discussed. It is argued that future research should use migration theories in a complementary rather than a competitive way.